Perceptions, relationships, expectations, and challenges: Views of communication and research for scientific dissemination in Brazilian Federal Institutes. - Tássia Galvão (Public Library of Science (PLoS), 2021)
Communicating Brazilian science still seems to be a challenge for journalists and researchers of public institutions of education and science. In this sense, this research aims to identify and analyze scientists' perceptions regarding the work of journalists, the relationship between these groups, the expectations, and the challenges of science communication in two Federal Institutes of Education in Brazil. We conducted a mixed study in the qualitative stage with the participation of 30 interviewees, and in the quantitative stage, journalists and researchers answered a questionnaire (n = 242). Our results indicated that the work of science communication is not carried out properly in both Institutes and that there is a lack of articulated work among both journalists, communicators, and researchers. The relationship between these groups needs to be built jointly. In this respect, the biggest challenges are to institutionalize science communication, establish a science communication plan, and overcome internal relationship barriers. Our results may underpin science communication policies and policies for scientific dissemination both institutional or even national levels.